Decellularized Human Maxillary Sinus Schneiderian Membrane as a Potential Scaffold for Tissue Engineering - Saeedeh KhajehAhmadi; Amin Rahpeyma; Nasser MahdaviShahri (Mashhad University of Medical Sciences, 2013)
Introduction: Biological matrix has received special attention in recent medical and biological researches. Cells of tissue are supported by extracellular matrix (ECM). Extracellular matrix is used as a scaffold for morphogenesis, proliferation, migration, and differentiation in tissue engineering. Extracellular matrix of natural tissues can be used as a scaffold for reconstructing biological tissues in tissue engineering. Human maxillary sinus membrane consists of cells and ECM which contain collagen, elastin, and proteoglycans. Collagen can be used as a natural scaffold via high level of biocompatibility. Materials & Methods: In this study, Human maxillary sinus membrane were decellularized by two techniques , physical method (liquid nitrogen) and chemical procedures via increment concentration of sodium dodecyl sulfate (SDS) in three groups. The samples were fixed with Bouin's fixator, and then were stained with Hematoxylin & Eosin. decellularised Human maxillary sinus membrane was evaluated with scanning electrone microscope.Results: Histological evaluation of decellularized scaffolds revealed that cells of the schneiderian membrane tissues were completely removed via concentration of 1% of SDS. Scanning Electrone Microscope (SEM) (Leo-VP1450, Germany) of the scaffolds indicated that collagen fibers of connective tissue remained intact. In 0.5 and 0.1% concentrations of SDS, few cells were observed at peripheral of ECM, so decellularization process was not complete. Conclusion: According to the results, scaffolds prepared from Human Maxillary Sinus Membrane could be used as a suitable scaffold for In vitro investigation and reconstruction and tissue engineering.